MENGKAJI KETERAMPILAN BERPIKIR KRITIS SISWA MENGGUNAKAN MODEL PROBLEM BASED LEARNING BERBANTUAN TEKNIK PROBING PROMPTING (PBL-PP) - Vitoria Venisia Pereira; Achmad Samsudin; Judhistira Aria Utama (LPPM Universitas Muhammadiyah Muara Bungo, 2023)
Critical thinking skills are one of the important elements that must be possessed by students. In learning, critical thinking skills have been applied in learning environments to address student challenges in the 21st century. This study aims to explore students' critical thinking skills during the learning process using the Problem-Based Learning (PBL) model assisted by the probing prompting technique. The method used in this study was a literature review, by analyzing and synthesizing several Physics education journals published in 2017-2022 which discussed critical thinking skills, Problem-Based Learning (PBL) models, and probing prompting techniques with the research sample being students at elaboration of junior, high school, and college students who have different levels of understanding. Based on the results of the 40 journals in this study, it was found that the PBL model assisted by the probing prompting technique is an innovative learning model that can be applied in active learning to improve critical thinking skills, which is one of the dimensions in the Pancasila student profile. This is because this model displays various problems that occur in everyday life, through a series of questions as a guide so that it can stimulate students to seek and find solutions to a problem. The results of this study can be used as recommendations for teachers in classroom learning activities to improve students’ critical thinking skills.